Optimised reversal without train-of-four monitoring versus reversal using quantitative train-of-four monitoring: An equivalence study - Wardhana, Ardyan; Kurniawaty, Juni; Uyun, Yusmein (Indian journal of anaesthesia, 2019)
Background and Aims: Less residual paralysis in recovery room was demonstrated when train-of-four (TOF) monitoring was applied. The aim of this study was to know whether optimisation of neostigmine reversal without TOF monitoring was equivalent to reversal using TOF monitoring. Methods: Seventy two patients, aged 18-60 years, undergoing elective surgery under general anaesthesia (sevoflurane and rocuronium) with intubation were randomised into two interventions: an optimised neostigmine reversal strategy without TOF monitoring (group A, n = 36) and a neostigmine reversal strategy using quantitative TOF monitoring (group B, n = 36). Per-protocol analysis was performed to compare incidence of residual paralysis in the recovery room between the two groups. Results: Six residual paralyses occurred in group A in the recovery room, whereas one case occurred in group B. The equivalence test showed that the 95% confidence interval of this study was outside the range of equivalence margin (15%). The absolute difference was 13.9%: standard error (SE) =0.068 (P = 0.107; 95% confidence interval (CI): 1%, 27.2%). No subjects had TOF ratio <0.70 in the recovery room. The TOF ratio in the recovery room did not differ between the two groups (mean difference: −2.58; P = 0.05; 95% CI: −5.20, 0.29). One respiratory adverse event occurred in this study. Conclusion: An optimised reversal strategy without TOF monitoring is not equivalent to a reversal strategy based on quantitative TOF monitoring. TOF monitoring should be used whenever applicable, although neostigmine is optimised.